NOBCChE News, Volume 10, Number 3 (National Organization for Black Chemists and Chemical Engineers, 1989)
June 1989 issue of NOBCChE News.
Keywords: National Organization for Black Chemists and Chemical Engineers; Chemists; Chemical engineers; African American chemists; African American engineers; Newsletters; Periodicals; Scientists, Black; African American scientists